Pre-service teachers’ readiness in implementing adapted physical education in a mainstream classroom - Ronel S. Peromingan; Ruben L. Tagare, Jr.; Ma. Flor Jessamine M. Andajao; Dexter T. Paclibar; Mary Ann A. Salazar; Elmer M. Labad; Emie S. Misil (Journal of Education and Learning (EduLearn), 2026)
This study investigates pre-service teachers’ readiness to implement adapted physical education (APE) in mainstream classrooms, focusing on essential competencies such as knowledge, adaptability, empathy, communication, safety awareness, assessment, and resilience. Utilizing a quantitative research design, specifically a correlational approach, the study engaged 112 respondents selected through simple random sampling from a leading state university in Southern Philippines. Data were collected using a researcher-made survey questionnaire that underwent pilot testing and reliability assessment. The analysis employed mean and Spearman’s rho correlation coefficient to explore the relationships among the different dimensions of readiness. The findings reveal that pre-service teachers are moderately ready to implement APE, with significant interrelationships identified among all competency areas. These results indicate a need for comprehensive teacher training programs that emphasize the interconnected nature of these competencies, suggesting that improvement in one area could enhance readiness across others. The study concludes that a holistic approach in teacher preparation is essential for developing competent educators capable of promoting equitable participation in physical education (PE) for all students, ultimately enhancing the quality of APE in mainstream settings.